LEVENORGESTREL INTRA UTRINE SYSTEM (LNG IUS) IN MENORRHAGIA: A THREE YEARS FOLLOWUP STUDY - Utman, Naeema; Faheem, Fouzia (Journal of Postgraduate Medical Institute, 2011)
Objective: To find the role of Levenorgestrel Intra uterine system (LNG IUS) in menorrhagia in women Methodology: This descriptive study was conducted in private setup and Gynaecology A unit, Lady Reading Hospital, Peshawar over a period of three years i.e., June 2004 to June 2007. The study population consisted of 60 women. All these women presented with heavy menstrual flow, having no contraindication for the device and consenting to Levonorgestrel Intra Uterine System after counseling. Those having organic cause for menorrhagia were excluded. Women were followed up at 6 week, 6 month and 12 month. Results: The mean age of the sample was 35.98+7.66 years. In the sample, multipara were 86.66%(n=52) and nulliparous were 13.33%(n=8); married were 91.66%(n=55) and unmarried were 8.33%(n=5). The indication for the device were menorrhagia in 75%(n=45) cases; women having intrauterine contraceptive device previously and currently having menorrhagia in 16.6%(n=10) cases; and others 8.33%(n=5) cases (women who are unfit for general anesthesia or having other co-morbidity i.e., asthma, uncontrolled diabetes). The acceptance rate was 80% (n=48) and discontinuation rate was 20%(n=12). In these 12 cases, expulsion of device, pelvic inflammatory disease and no improvement in the condition was seen in 10%(n=6), 3.3%(n=2) and 6.6%(n=4) respectively. At follow up 3.3%(n=8) women had irregular period while 73.3%(n=44) were amenrroheic and13.33%(n=8) women had regular period at the end of one year. Conclusion: Levonorgestrel IUS is one of the effective treatment modality which can be used for menorrhagia with reasonable efficacy over period of three years.